Evaluation of the Contribution to Local Development through Agritourism Routes in Calixto García - Lisbet Eunice Pérez Anzardo; Francisco Infante Estrabao; Ana Gloria Madruga Torres; Irina Reyes Martínez; Lic. Yudismay García Velázquez (Budapest International Research and Critics University, 2026)
The diversification of agriculture and its linkage with tourism represent a strategic alternative to stimulate local development in rural areas with productive and heritage potential. The objective of this research was to design an instrument to evaluate the contribution of agritourism routes to local development in the municipality of Calixto Garcia. A mixed approach was applied, predominantly qualitative, supported by theoretical methods such as historical-logical, analytical-synthetic, and inductive-deductive, as well as empirical methods including scientific observation, unstructured interviews, and expert judgment. The unit of analysis was the municipality of Calixto Garcia, complemented by local actors linked to the agricultural and tourism sectors. The results revealed that the supply of agritourism routes remains incipient and limited by scarce technical and tourism training; however, the estimation of socioeconomic indicators showed significant impacts on employment, income, and community cohesion. It is concluded that the proposed instrument constitutes a practical tool to comprehensively assess the contribution of agritourism routes to local development, guide decision-making, and promote improvement actions aimed at the economic, social, and environmental sustainability of the territory.